Anatomical site-wise distribution of upper aerodigestive tract malignancies in a rural population - Shariff, Mudassar A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Upper aerodigestive tract malignancies constitute approximately 4% of all malignancies. These include cancers of the various sites of the upper aerodigestive tract where malignant lesions can be found such as the nasal cavity, paranasal sinuses, nasopharynx, oral cavity and it’s sub-sites, oropharynx, larynx and hypopharynx. Malignancies of these sites are found to be common in people from lower socio-economic strata. Tobacco and alcohol are considered as risk factors for it’s development. Methods: A cross-sectional study was conducted in the outpatient section of Department of ENT, at Chamarajanagar Institute of Medical Sciences and Hospital, Chamarajanagar, India, for a period of 1 years 10 months from October 2014 to July 2016. During the study period, 100 cases that were diagnosed as having upper aerodigestive tract malignancy by histopathology were included in the study group. The aim of this study is to determine the epidemiology, clinical features and anatomical site-wise distribution of malignancy in the study group. Results: Oral cavity was the commonest site where malignancy developed in the upper aerodigestive tract followed by the larynx. Malignant disease was more common in males and in the elderly. Majority of the patients who developed malignancy had history of tobacco and alcohol consumption. Conclusions: Oral cavity malignancy is common in rural population, is associated with tobacco chewing and is more common in elderly male.